2015
DOI: 10.1037/a0037530
|View full text |Cite
|
Sign up to set email alerts
|

Mild test anxiety influences neurocognitive performance among African Americans and European Americans: Identifying interfering and facilitating sources.

Abstract: The current study examined ethnic/racial differences in test-related anxiety and its relationship to neurocognitive performance in a community sample of African American (n = 40) and European American (n = 36) adults. The authors hypothesized the following: (a) Test-anxiety related to negative performance evaluation would be associated with lower neurocognitive performance, whereas anxiety unrelated to negative evaluation would be associated with higher neurocognitive performance. (b) African American particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Other studies have shown that test anxiety among African American individuals is more likely to be negatively correlated with performance on neuropsychological measures compared with European Americans (Thames et al, 2015). Concern about how poor performance would be perceived by others and self-image were the primary sources on anxiety for African Americans in the study, whereas European Americans in the study experienced anxiety related to not being well prepared for the test (Thames et al, 2015). Even outside of the testing situation, higher levels of perceived discrimination-related chronic stress are associated with lower performance on tests of episodic memory and perceptual speed, even after controlling for vascular risk factors, age, sex, and education (Barnes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that test anxiety among African American individuals is more likely to be negatively correlated with performance on neuropsychological measures compared with European Americans (Thames et al, 2015). Concern about how poor performance would be perceived by others and self-image were the primary sources on anxiety for African Americans in the study, whereas European Americans in the study experienced anxiety related to not being well prepared for the test (Thames et al, 2015). Even outside of the testing situation, higher levels of perceived discrimination-related chronic stress are associated with lower performance on tests of episodic memory and perceptual speed, even after controlling for vascular risk factors, age, sex, and education (Barnes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…8 A combination of the emotional and cognitive components has been widely studied using a variety of tools in many different student populations [9][10][11][12][13][14] ; however, the cognitive or worry component of test anxiety is the focus of this research.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results of linear regressions suggested high levels of test anxiety were associated with more advantageous decision making on Block 2 of the IGT, during the transition from decision making under ambiguity to decision making under risk. By contrast, previous research has indicated test anxiety is typically associated with decreases in task performance (Ng & Lee, 2015;Thames et al, 2015). It is possible that individuals with high test anxiety (or high social concerns/stress) paid attention to signals of punishment/losses, leading to improved performance earlier on the IGT.…”
Section: Discussionmentioning
confidence: 83%
“…Test anxiety, of which math anxiety is a specific form, may affect the decision-making process. Test anxiety occurs in general testing or evaluative situations (Hembree, 1988), with high levels negatively affecting performance across a variety of tasks including neuropsychological tests (Chapell et al, 2005; Musch & Broder, 1999; Ng & Lee, 2015; Sarason, 1984; Seipp, 1991; Thames et al, 2015). Test anxiety can also negatively affect decision making, in that individuals with test anxiety sought out increasing amounts of redundant information prior to making a decision (Nichols-Hoppe & Beach, 1990).…”
Section: Test Anxiety Math Anxiety and Decision Makingmentioning
confidence: 99%